the Impact of semi-sport games in developing the attention skill of those with learning difficulties - Bensaid, mohammed el amin; belgoul, fathi (sports creativity, 2025)
The objective of this study is to identify the Impact of semi-sport games in developing the attention skill of those with learning difficulties . of the study in the different variables (attention difficulties, reading difficulties, writing difficulties, calculation difficulties) and sample. Therefore, in an attempt to achieve the objectives of the study we tend to base it on the experimental approach, where the scale was distributed to the teachers, where the sample of the study on (15) studentsat the center of adaptation of Ben Aknoun ,The researchers also recommend the use of semi-sport games to develop the different mental abilities like attention and reduce learning difficulties